Belarus under Lukashenka adaptive authoritarianism - Frear, Matthew (BASSES-Routledge series on Russian and East European studies, 2019)
1. Introduction -- Why Belarus? The research context -- From Polatsk to Perestroika -- From Soviet socialist republic to sovereign state -- Outline of the book -- Notes -- 2. Adaptive authoritarianism: A conceptual framework -- Classifying non-democratic regimes -- Legitimizing non-democratic rule -- Implementing non-democratic rule -- Challenging non-democratic regimes -- Conclusion -- Notes -- 3. Personalization of power under Lukashenka: Institutions -- The constitution before Lukashenka -- Parliament and the legislative functions -- Government and the executive functions -- Constitutional court and the judiciary -- Local government -- National economy -- Conclusion -- Notes -- 4. Personalization of power under Lukashenka: Elites -- Co-opting the post-Soviet elites -- Reliable old associates -- New faces and factions -- The benefits of patron-client relations -- Conclusion -- Notes -- 5. Ruling Belarus: Public consent and policy adaptation -- Appealing to Lukashenka's traditional support base -- Adaptive government policies -- Conclusion -- Notes -- 6. Ruling Belarus: State coercion and pre-empting democracy -- Persecution of opponents -- Pre-emptive authoritarianism -- Conclusion -- Notes -- 7. Challenging adaptive authoritarianism: Players -- Categorizing opposition to non-democratic rule -- Political opposition in Belarus -- Civic opposition in Belarus -- Opposition alliances and coalitions -- Conclusion -- Notes -- 8. Challenging adaptive authoritarianism: Tactics -- Internal divisions -- Rejecting legitimacy and parallel political bodies -- Participation under electoral authoritarianism -- Contentious politics under Lukashenka -- Conclusion -- Notes -- 9 Conclusion -- Appendix A: Economic indicators under Lukashenka